THE ANALYSIS OF THE INFLUENCE OF INFLATION, EXCHANGE RATE AND BI RATE TOWARDS THE JAKARTA COMPOSITE INDEX IN THE INDONESIA STOCK EXCHANGE - Risma Dwi Agustin; Dedi Suselo (Universitas Islam Lamongan, 2022)
The capital market is often used as a benchmark for a country's economy that influences the investment activities in macroeconomics which is reflected in some indicators like inflation rates, exchange rates, and the BI rate. This article aims to find out and analyze the influence of inflation, exchange rate, and the BI Rate on the Jakarta Composite Index. This study used a quantitative approach with the type of associative. The results of this study showed that there is no significant influence between the inflation towards the JCI, but there is an influence between the exchange rate and the BI Rate towards the JCI. Simultaneously these variables, like Inflation, Exchange Rate, and BI Rate have a positive and significant influence towards the JCI.